Male genitalia of the lower Brachycera (Diptera). - Nagatomi, Akira (Contributions to Entomology = Beiträge zur Entomologie, 1984)
The male genitalia of the lower Brachycera are discribed and illustrated, dealing with a total of 37 species and 33 genera. Keys to 13 families of the lower Brachycera and 18 genera of the Rhagionidae are presented but are not arranged from the phylogenitical point of view. To determine the phylogenetical relationship on the basis of the male genitalia allone is difficult. Several questions are discussed as to the primitive, systematic positions of some families, and the validity of small families.